OS DISCURSOS DOS CANDIDATOS A PRESIDENTE DA REPÚBLICA NO PLEITO DE 2014 EM UMA PERSPECTIVA BAKHTINIANA - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
Based on the dialogical conception of language, the objective of this work is to establish dialogic relations in statements produced during the presidential elections of 2014. We base ourselves on concepts formulated by the Bakhtin Circle for proposing a sociological conception of language which understands that real individuals communicate through concrete statements that do not form in the context, in a responsive dialogical process in which each word is a sign loaded with ideological value that can assume different values tonalities. In our analysis we present the statements made by the candidates best placed in the polling surveys and in the first round of the elections. We chose the most significant statements for the electoral process, belonging to different discursive: the slogans of Dilma Rousseff (PT), Aécio Neves (PSDB) and Eduardo Campos (PSB), a letter written at the beginning of the second round by Aécio Neves (PSDB), support positions for the second round of Marina Silva (PSB) for candidate Aécio Neves (PSDB) and speech by Dilma Rousseff (PT). We emphasize the dialogical relations established between utterances, because each utterance is a link in the discursive chain that can’t be separated from the other links because it is only part of an infinite chain of statements with which it maintains a responsive attitude. Our analysis is based on the principle that every word is an ideological sign with different values. Thus, in the analyzed statements we observe that the change sign presents different values according to the political group to which it belongs. During the analysis we also observe that every statement assumes an evaluative position and that it serves a project to say based on the worldview of its speaker/writer, who makes the necessary linguistic decisions in view of their interlocutors and their extraverbal context.
Keywords: Enunciado; Signo; Ideologia; Dialogismo; Statement; Sign; Ideology; Dialogism; CNPQ::LINGUISTICA, LETRAS E ARTES